Introducing a Method for Calculating Carbon Emission Reduction on the Seagrass Ecosystem for Indonesia's Low Carbon Development Initiative. Issue 1 (June 2021) - Wahyudi, A J; Prayudha, B; Hafitz, M; Alifatri, L O; Hernawan, U E; Salatalohi, A; Febriani, F
Abstract: The increase of anthropogenic carbon dioxide (CO2 ) since the industrial revolution era affects the global carbon cycle and triggers climate changes. Indonesia has ratified the Paris Agreement and declared the emission reduction for climate action (Sustainable Development Goal 13) up to 29% (independently) or 41% (with international support) in 2030 relative to the business as usual (BAU) scenario. The effort to achieve this target is implemented on Low Carbon Development Initiative (LCDI) starting in 2020. LCDI adopts marine and fisheries as one of the implementing sectors that focus on blue carbon. To implement the activities as part of the carbon emission reduction within the LCDI, we have to establish a calculation method that should be measurable, reportable, and verifiable (MRV). The present article introduces the MRV method for calculating the carbon emission reduction for the Conservation/Protection Seagrass Ecosystem's climate change mitigation activity on Marine Protected Area (MPA) . We present how to calculate the baseline emission (business as usual), emission leakage when implementing the activity, and emission reduction. A case study on seagrass meadows of Kepulauan Seribu MPA is presented for the trial of the introduced method and formula. Using the proposed method is reliable enough to estimate carbon emission reduction from seagrass conservation activity within the MPA. We can calculate the carbon emission will reduce 4.35 tC relative to the BAU on Kepulauan Seribu MPA by 2030.